2013
DOI: 10.1007/s00464-013-2904-9
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic submucosal dissection as a treatment for gastric subepithelial tumors that originate from the muscularis propria layer: a preliminary analysis of appropriate indications

Abstract: BackgroundEndoscopic submucosal dissection (ESD) is a well-established method for the treatment of gastrointestinal epithelial tumors. However, the treatment of gastric subepithelial tumors (SETs) that originate from the muscularis propria layer still depends primarily on surgical techniques. We evaluated the appropriate indications for ESD in the treatment of SETs that originate from the muscularis propria layer.MethodsThirty-five patients with gastric SETs that originate from the muscularis propria layer who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 16 publications
2
53
0
Order By: Relevance
“…In two studies which used similar inclusion criteria and methods, Chun et al (2013) reported that the complete resection rate for SMTs originating in the MP layer of SMTs was 74.3%. These authors also reported that a positive rolling sign (tumor having a narrow muscle connection or no muscle connection) and a tumor size >2 cm were closely related to the complete resection rate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In two studies which used similar inclusion criteria and methods, Chun et al (2013) reported that the complete resection rate for SMTs originating in the MP layer of SMTs was 74.3%. These authors also reported that a positive rolling sign (tumor having a narrow muscle connection or no muscle connection) and a tumor size >2 cm were closely related to the complete resection rate.…”
Section: Discussionmentioning
confidence: 99%
“…The perforation rate for tumors with a wide muscular connection was significantly higher than that for tumors with a narrow muscular connection (34.8% vs. 5.0%; P=0.044). Chun et al (2013) studied 35 SMTs which originated in the MP layer, and reported that perforation was more likely to occur when ESD was used to treat an immobile tumor (40% vs. 0% for highly mobile tumors), whereas the tumor's connection with the fourth layer was not related to the perforation rate. A wide muscular connection was a common finding among growing intraluminal tumors originating in the deep MP layer (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endoscopic submucosal excavation (ESE) and submucosal tunneling endoscopic resection (STER) provide definitive histological diagnosis as well as therapeutic approaches for GI submucosal tumors (SMTs) arising from muscularis propria (MP), which used to be a diagnostic dilemma [2]. While ESE is basically a technical extension of ESD-just excavating deeper into MP [3][4][5][6][7]; STER uses a submucosal tunnel as an operating space to resect targeted tumor. This recently rising tunneling technique possesses an obvious advantage of preserving the integrity of covering mucosa as a barrier against air/ liquid leakage.…”
mentioning
confidence: 99%